Pengaruh Strategi Pembelajaran Aktif Tipe Giving Question and Getting Answer terhadap Hasil Belajar Bahasa Indonesia Siswa Sekolah Dasar - Afdal; Hani Subakti; Febriyanti Sigalingging (Magister Pendidikan Bahasa dan Sastra Indonesia, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mulawarman, 2020)
This study aims to look at the effect of an active learning strategy type giving questions and getting answers to Indonesian primary school students' learning outcomes. This study uses an experimental research method in which there are treatments for the control class and the experimental class. The final results of the study showed the results of the analysis of the influence of active learning strategies type giving a question and getting an answer to the results of Indonesian language learning of third-grade students at SDN 002 Sungai Pinang, Samarinda City in the affective domain had an average affective assessment in the good predicate. This can be seen from the results of the hypothesis test thitung is 1.208 with ttable is 2.006 so that it can be written tcount <ttable (1.208 <2.006), which can be interpreted as Ha is rejected and H0 is accepted. Based on research results in the cognitive realm have the final test results (post-test), the experimental class obtained an average value of 77.69, the highest value of 100 and the lowest value of 60. The final test results (post-test), the control class obtained an average value of 49.64, the highest value is 80, and the lowest value is 20. This can also be seen through the hypothesis test results using the t test (independent sample t test), the tcount = 10.175 and ttable = 1.67. Hypothesis test tcount> ttable (10,175> 1,67). Based on the description, it can be concluded that there is an influence of active learning strategy type giving a question and getting an answer to Indonesian students' learning outcomes in the cognitive realm of class III in SDN 002 Sungai Pinang Samarinda City in 2019/2020. Hence, it shows that the hypothesis is accepted.